Color Stability and Antioxidant Activity of Red Roselle (Hibiscus Sabdariffa L.) Calyx Infuse - Sholika Sari, Trisiyana; Kusumawati, Idha; Isnaeni, Isnaeni (Universitas Airlangga, 2023)
The roselle flower (Hibiscus sabdariffa L.), was known as a potential functional food source because of its antioxidant and antibacterial properties. Apart from that, it was also used as a natural dye because of its red color. Antioxidant compounds in roselle flowers included neo-chlorogenic acid, chlorogenic acid, crypto- chlorogenic acid, routine, and isoquercitrin. The high content of these antioxidant compounds often causes color instability. For this reason, this research would analyzed the effect of temperature and long storage on color changes and the antioxidant activity of a red roselle flower infusion. Storage conditions were carried out with three temperature variations, namely cold temperature (2–8℃), cool temperature (8–15℃), and room temperature (15–30℃), with a long storage of 8 days. The stability parameters used were color changes and activity as an antioxidant. Color changes were measured using a chromameter, while the antioxidant activity was measured by the IC50 value using the DPPH method. The principle of this method was based on a purple color change reaction, which faded, and then the inhibitory intensity against DPPH was measured using UV-Vis spectrophotometer. It was found that the color values had significant differences visible from the first day storage at the room temperature (30℃), cool temperature (11℃), and cold temperature (6℃). Thus, there was an influence of temperature and long storage on the color change of boiled red roselle flower calyx. A significant decrease in activity was seen on the first day storage at room temperature (30℃) and third day storage at cool temperature (11℃). Meanwhile, at cold temperatures (6℃), there was no significant effect on the reduction in activity from boiling red roselle flower calyx for up to 8 days of storage. Keywords: Red Rosela, Stability, Infuse, Color, Antioxidant